The CARMENES search for exoplanets around M dwarfs: two planets on opposite sides of the radius gap transiting the nearby M dwarf LTT 3780 - Nowak, Grzegorz; Molaverdikhani, Karan; Henning, Thomas; Kaminski, Adrian; Kemmer, Jonas; Kürster, Martin; Quirrenbach, Andreas; Reffert, Sabine; Schlecker, Martin; Stock, Stephan; Trifonov, Trifon (Astronomy and astrophysics, 2020)
We present the discovery and characterisation of two transiting planets observed by the Transiting Exoplanet Survey Satellite (TESS) orbiting the nearby (d⋆ ≈ 22 pc), bright (J ≈ 9 mag) M3.5 dwarf LTT 3780 (TOI–732). We confirm both planets and their association with LTT 3780 via ground-based photometry and determine their masses using precise radial velocities measured with the CARMENES spectrograph. Precise stellar parameters determined from CARMENES high-resolution spectra confirm that LTT 3780 is a mid-M dwarf with an effective temperature of Teff = 3360 ± 51 K, a surface gravity of log g⋆ = 4.81 ± 0.04 (cgs), and an iron abundance of [Fe/H] = 0.09 ± 0.16 dex, with an inferred mass of M⋆ = 0.379 ± 0.016M⊙ and a radius of R⋆ = 0.382 ± 0.012R⊙. The ultra-short-period planet LTT 3780 b (Pb = 0.77 d) with a radius of 1.35−0.06+0.06 R⊕, a mass of 2.34−0.23+0.24 M⊕, and a bulk density of 5.24−0.81+0.94 g cm−3 joins the population of Earth-size planets with rocky, terrestrial composition. The outer planet, LTT 3780 c, with an orbital period of 12.25 d, radius of 2.42−0.10+0.10 R⊕, mass of 6.29−0.61+0.63 M⊕, and mean density of 2.45−0.37+0.44 g cm−3 belongs to the population of dense sub-Neptunes. With the two planets located on opposite sides of the radius gap, this planetary system is anexcellent target for testing planetary formation, evolution, and atmospheric models. In particular, LTT 3780 c is an ideal object for atmospheric studies with the James Webb Space Telescope (JWST).
Gesehen am 15.04.2021